Qualitative mapping of cerebral blood flow and functional localization with echo-planar MR imaging and signal targeting with alternating radio frequency. - Edelman, R; Siewert, B; Darby, D; Thangaraj, V; Nobre, A; Mesulam, M; Warach, S (1994)
PURPOSE: To create qualitative maps of cerebral blood flow (CBF) with the EPISTAR (echo-planar imaging and signal targeting with alternating radio frequency) technique. MATERIALS AND METHODS: The EPISTAR technique was performed in a pig model of hypercapnia and then tested in 26 volunteers by using various paradigms for cortical activation. Echo-planar images were acquired with and without use of a radio-frequency inversion pulse applied to inflowing arterial spins. A qualitative map of CBF was then created by subtracting the image obtained without the radio-frequency pulse from that obtained with the radio-frequency pulse. RESULTS: Progressively more distal portions of the tagged vessels were seen as the inflow time was lengthened until cortical enhancement was seen for inflow times of approximately 1 second or longer. Signal intensity increases from rest to sensorimotor activation ranged from 13% to 193%. CBF changes in the motor strip, primary visual cortex, and the motor area for eye movements were well localized to the cortical gray matter ribbon. CONCLUSION: The EPISTAR technique is a rapid, noninvasive means for creating qualitative maps of CBF.